The Effectiveness of Virtual Class With Zoom Meeting in Teaching Evaluation Lectures Indonesian - Trisna Helda; Edwar Kemal; Yulia Pebriani; Silvia Marni (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2022)
Online Lectures are the main means of learning during the Covid-19 pandemic. It was unavoidable at that time, the campus was conducting online lectures from home due to the Covid-19 pandemic, but lecturers and students continued to conduct online-based lectures or Virtual Class through various applications, one of which was Zoom Meeting. The application of Zoom Meetings is still very common for students because usually lecturers teach face-to-face. The purpose of this article is to find out the effectiveness of implementing Virtual Class with Zoom Meetings in Indonesian language teaching evaluation lectures. The method used is quantitative in the form of filling out questionnaires through Google Forms for students of the Indonesian Language and Literature Education Study Program at PGRI West Sumatra University who are taking the Indonesian Language Teaching Evaluation course in the odd semester of 2021/2022 totaling 34 students. From the results of the descriptive survey, it was found that the Zoom Meeting was less effective in evaluating Indonesian language teaching, but it was effective in virtual classroom learning and could be used as an online learning application. So it can be concluded that students can still continue their lectures in a virtual class or indirectly by using a zoom meeting in the process of evaluating Indonesian language teaching evaluation lectures.